Facing Inflated Rules – Experimental Evidence from Threshold Public Goods Games - Christian Grund; Philipp Monschau (Institute of Labor Economics (IZA), 2025)
We study the role of purpose-based rules for behavior and outcomes in a threshold public good game. Rules can be sufficient or even inflated in terms of proposing a fulfilling behavior. We conduct a lab experiment to describe the implications caused by the inflation of a rule. Our study shows that inflated rules are obeyed less. Yet, rule-following occurs also with inflated rules which leads to lower efficiency regarding exactly providing the threshold. A fair share option can help to coordinate efficiently. We complement our analysis by the investigation of the role of the implemented rules for the ex-post optimal behavior, i.e. evaluating the individual contribution depending on the individual payoff.
Keywords: C9; H41; M5; 330; rule-following; coordination; cooperation; groups; thresholds; public goods